EXTRACTING SILVER FROM ANODE SLIME AFTER LEAD AND GOLD SEPARATIONS - Isyatun Rodliyah; Siti Rochani (Indonesian Mining Journal, 2017)
Anode slime, a byproduct from the process of copper electrorefining into the copper cathode, contains several valuable elements that can be extracted after Cu and Pb separations. Another alternative route for extracting the precious metals is still needed in terms of gaining more economical route. This research aims to seek the new route to extract the precious metals, especially silver from anode slime. In these experiments, the anode slime was obtained from PT Smelting Gresik. The lead was separated to produce the residue which was then chlorinated to extract the gold. Later the residue was used for extracting the silver by dissolving it in ammonium hydroxide solution with varying time dissolutions and concentrations and later dissolving in hydrochloric acid to form silver chloride which was reduced to metallic silver. These experiments had two trials. The first one related to directly using residual chlorination after gold separation and the second one employed the same residual chlorination but processed through de-chlorination by adding sodium carbonate. The result showed that the highest silver recovery of 53.56% related to 5 M ammonium hydroxide concentration, the temperature of 30°C, dissolution time of 60 minutes. Recovery of 53.78% was achieved at 7 M ammonium hydroxide, the temperature of 30°C, dissolution time of 60 minutes. The feed of those experiments came from direct residual chlorination, while chlorination residue that underwent de-chlorination produced silver recovery of 94.95% with leaching conditions of 5 M ammonium hydroxide, the heating temperature of 30°C and leaching time of 60 minutes. The latest recovery was relatively high resulted in the process could be scaled up to a continuous system.